Biomechanical modeling of spatiotemporal bacteria-phage competition - Andrés Valdez; Hui Sun; Howard Howie Weiss; Igor Aranson (Communications Physics)
Abstract Bacteriophages are viral predators of bacteria. Understanding the bacteria-phage competition is crucial for horizontal gene transfer and treatment of antibiotic-resistant bacterial infections. Here, we investigate the interaction dynamics between common rod-shaped bacteria such as Escherichia coli or Pseudomonas aeruginosa and lytic phages within 2D and 3D environments. Our computational study is based on established experimental observations of bacteria-phage interactions. A lytic phage effectively kills bacterial cells in a colony, leading to significant consequences for its morphology and expansion. Through computational modeling, we observe that phage interactions with bacteria produce phage-plaque regions characterized by cell death, reorganization, and altered colony growth dynamics. As phages predate, surviving cells tend to re-align toward the phage-affected region, forming a more ordered structure. This reordering effect not only reduces the radial spread of the colony but, in highly virulent scenarios, generates an inflow of cells toward the phage-plaque, effectively “devouring” portions of the colony. Our work highlights how phages control the self-organization of proliferating active matter and offers insights into targeted approaches for managing bacterial populations in biofilm-associated environments.